2009
DOI: 10.1007/s11747-009-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

The service quality-satisfaction link revisited: exploring asymmetries and dynamics

Abstract: This study provides deeper insight in the link between service quality and customer satisfaction. The traditional assumption of a linear relationship is challenged by exploring asymmetries and dynamics. The simultaneous influence of service quality and customer experience on satisfaction is examined by means of nonlinear structural equation modeling. Results show that functional-utilitarian quality attributes (availability, efficiency, fulfillment, and privacy) lose their capability to delight customers as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 65 publications
6
126
0
8
Order By: Relevance
“…Online shopping experience has been identified as one of the most important factors affecting e-commerce traffic and sales (Menon and Khan, 2002;Falk et al, 2010). Mounting evidence would suggest that price discounts are no longer enough to attract or retain customers; in fact, the shopping experience motivates online customers (Kim et al, 2009).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Online shopping experience has been identified as one of the most important factors affecting e-commerce traffic and sales (Menon and Khan, 2002;Falk et al, 2010). Mounting evidence would suggest that price discounts are no longer enough to attract or retain customers; in fact, the shopping experience motivates online customers (Kim et al, 2009).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Previous research has defined utilitarian experiences as those providing instrumental, practical, and functional convenience, whereas hedonic experiences have been viewed as more fun, playful, experimental, and enjoyment-related (Childers et al, 2002;Falk et al, 2010). Past research has established that websites offering utilitarian experiences facilitate consumers' information processing and goal-attainment and are positively associated with the effectiveness of the website (Cyr and Head, 2013), whereas websites offering hedonic experiences furnish sensory gratification and are positively associated with enjoyment (Falk et al, 2010;Wang et al, 2011). That is, utilitarian websites have been shown to satisfy utilitarian and more pragmatic needs ( Van der Heijden, 2004).…”
Section: Hedonic and Utilitarian Websitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of service quality on behavioral intentions takes on different forms: direct effect, indirect effect through satisfaction, or moderating effect by satisfaction (Falk, Hammerschmidt, & Schepers, 2010;Bou-Llusar et al, 2001;Woodside, Frey, & Daly, 1989). For the direct effect, many studies in different industries have shown that service quality is an antecedent to behavioral intentions (Li, Huang, & Yang, 2011;Boshoff & Gray, 2004;Bou-Llusar et al, 2001); Parasuraman et al, 1985Parasuraman et al, , 1988Zeithaml et al, 1996).…”
Section: Linking Service Quality Satisfaction and Behavioral Intentmentioning
confidence: 99%